2020
DOI: 10.1097/mlr.0000000000001354
|View full text |Cite
|
Sign up to set email alerts
|

Early Performance of Hospital Value-based Purchasing Program in Medicare

Abstract: Background: Under the Affordable Care Act, the Centers for Medicare and Medicaid Services has greatly expanded inpatient fee-for-value programs including the Hospital Value-based Purchasing (HVBP) program. Existing evidence from the HVBP program is mixed. There is a need for a systematic review of the HVBP program to inform discussions on how to improve the program’s effectiveness. Objective: To review and summarize studies that evaluated the HVBP progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
0
24
2
Order By: Relevance
“…The value-based program models are designed to incorporate patient-centered outcomes to improve the quality of care and incentivize providers in a reliable and effective way. [38][39][40] The present study found that the teach-back method during the interaction between a patient and provider achieved favorable patient outcomes. However, only 25% of the patient population with diabetes had consistent teach-back experience during their visits to care.…”
Section: Discussionmentioning
confidence: 69%
“…The value-based program models are designed to incorporate patient-centered outcomes to improve the quality of care and incentivize providers in a reliable and effective way. [38][39][40] The present study found that the teach-back method during the interaction between a patient and provider achieved favorable patient outcomes. However, only 25% of the patient population with diabetes had consistent teach-back experience during their visits to care.…”
Section: Discussionmentioning
confidence: 69%
“…and a disproportionate burden on safety net providers [8] Similarly, the impact of HVBP and HACRP is not promising. Multiple studies have examined the impact of HVBP [9]; most found no impact on a wide range of targeted quality metrics, with modest evidence of improvements in pressure ulcers [10] and 30-day pneumonia mortality rates [11]. Early studies of the HACRP suggested improvements in hospitalacquired conditions, [12] but more recent studies suggest there is no clear relationships between receipt of HACRP penalties and hospital quality of care [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Concern about the growing spending trend in healthcare (Dieleman et al 2020) has prompted clinical and health policy decision makers to continually assess benefits and value of new treatments and care processes with an objective to control costs without sacrificing quality of care (Blumethal and Abrams 2020;Baicker and Chandra 2020). Rising healthcare costs are a national problem, and as part of efforts to control costs, studies to assess the effect of systems changes on costs abound (Hong et al 2020;Farford et al 2019). However, few cost studies report a formal power analysis, and the literature is silent on questions related to the magnitude of cost.…”
Section: Introductionmentioning
confidence: 99%